A gateway to complexity: A cross-linguistic comparison of child bilingual speech - Quick, Antje Endesfelder; Gaskins, Dorota; Bailleul, Oksana; Frick, Maria; Palola, Elina (International Journal of Bilingualism, 2021)
Objectives: This study investigates monolingual and code-mixed utterances in four bilingual children with different language combinations (German–English, English–Polish, Finnish–English, and French–Russian) in terms of utterance lengths (MLUs) and complexities offering a usage-based (UB) explanation based on cognitive mechanisms. Methodology: Utterances from four different child bilingual corpora were extracted and coded for individual monolingual languages and bilingual utterances. Data and analysis: 35.441 utterances between the age of 2–4 were analyzed in terms of MLU and syntactic complexity. Findings/conclusions: Results showed that for all children monolingual MLUs and complexities reflect their input situations: the more input in one language, the longer and more complex those utterances were. However, in all four children code-mixed utterances were longer and more complex from the beginning of the recordings. Implications: This is the first study that systematically compares MLU scores and complexities of monolingual and bilingual utterances taking diverse language combinations into account and offering a UB explanation based on chunking and entrenchment processes as a new alternative for further research in bilingualism.
CRIS-Team Scopus Importer:2022-11-17
Keywords: bilingual children; Code-mixing; usage-based approach; utterance length